100-YEARS ANNIVERSARY OF THE INSTITUTE OF EPIDEMIOLOGY AND MICROBIOLOGY - L. I. Kolesnikova (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
This paper is about 100 years history of the Institute of the epidemiology and microbiology (Irkutsk), development of scientific researches and practical help to the public health.